The mechanism and predictors between mindfulness and flow state in elite athletes - Chen, J. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Background: Mindfulness interventions have been proved a benefit to promote flow stated and competitive anxiety in elite athletes. However, few studies explored possible mechanisms between those factors and also less is known about if there is any baseline condition as predictors to predict the better outcomes. Methods: 40 elite athletes of national level were recruited to participate 4 weeks workshop of Mindfulness Sport Performance Enhancement (MSPE). They were evaluated based on mental health condition (i.e., anxiety, depression, and sleep condition) and the outcome variables were flow state and competitive anxiety (i.e., confidence, somatic anxiety, and cognitive anxiety) at pre- and post-workshop. Results: We found that trait mindfulness mediated the relationship between all three aspects of competitive anxiety with the flow state, and the cognitive anxiety among them has even reached a fully mediated effect. However, the baseline mental health condition did not reach significance to predict flow enhancement after MSPE. Conclusion: Our findings suggest the mechanism that competitive anxiety negatively related to flow state via trait mindfulness. The baseline mental health is not a good predictor of MSPE intervention and future research should investigate possible predictors other than anxiety, depression, and sleep condition.